SEMI PURIFIKASI DAN KARAKTERISASI ENZIM PROTEASE Bacillus sp. - Elidar Naiola; Nunuk Widhyastuti (The East Java Biological Society, 2007)
The aim of the research was to find the partial purified of enzyme protease from Bacillus sp. The crude enzyme of protease was produce in rice brand medium (100 gram of rice brand in a liter tofu liquid waste). The enzyme was semi-purified by the procedure of precipitation using ethanol in different percentages of saturation, gel filtration using Sephadex G 100 and Ion Exchanged Chromatography using DEAE Sephadex A50. Specific activities of the enzyme during purification were 5.71 U/mg (crude enzyme); 6.75 U/mg (ethanol precipitations); 37.16 U/mg (gel filtration) and 43.02 U/mg (Ion Exchanged Chromatography). The optimum temperature for enzyme reaction was 45–50 °C, while the optimum pH was 7.0–8.0. Protease was relatively stable after heating until 37–50 °C for 60 minutes. Metal ions had different effects to the enzyme. CaCl2, FeCl3, MnCl2, ZnCl2 and MgCl2 increased enzyme activity, CdCl2 and HgCl2 gave an inhibitory effect, and another of metal ions had no effects to the enzyme.